Penggunaan Keputusan Pembayaran QRIS Sebagai Dompet Digital - Dwi Kusuma, Arya Putra (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2024)
This research aims to examine whether usefullness and convenience influence QRIS (Quick Response Code Indonesia Standard) payment decisions as a digital wallet for students of the Faculty of Economics and Business at Universitas Wijaya Kusuma Surabaya, either partially or simultaneously. This research method uses a descriptive quantitative approach and questionnaires distributed to 100 students as primary data. Researchers use the purposive sampling technique, and the analytical method is multiple linear analysis. This research uses two independent variables and one dependent variable. Independent variables use Usefullness (X1) and Ease of Use (X2) and use payment decisions (Y) as the dependent variable, and data processing uses SPSS 23. Results obtained that the Ease of Use variable has the most dominant influence on QRIS payment decisions as a digital wallet with a value of 35.4%. The utility variable shows a value of 26.9%, which means that this variable affects the payment decision variable, which means that all independent variables have a significant effect on QRIS payment decisions as digital wallets for students of the Faculty of Economics and Business, Universitas Wijaya Kusuma Surabaya